The relative role of religiosity in radicalization: how orthodox and fundamentalist religiosity are linked to violence acceptance - Demmrich, Sarah; Hanel, Paul H. P. (Frontiers in Social Psychology, 2024)
The role of religiosity in radicalization is a topic of intense debate. To avoid essentializing religion, it is crucial to include a variety of factors that can explain radicalization beyond religiosity. The present study aligns with this approach by building upon the three Ps of radicalization (push, pull, personal factors). It examines the relative role of various forms of religiosity (pull factors) in radicalization within the context of social structure, perceived deprivation (both push factors), and demographic variables (personal factors). We analyzed previously collected data comprising a sample of 1,048 Muslims with Turkish migration background in Germany. Acceptance of active and reactive violence as indicators of radicalization with demography, social-structure position, perceived deprivation, and different forms of religiosity (individual, collective, orthodox, fundamentalist religiosity) were used as predictors. Individual religiosity was a protective factor against reactive violence when controlling for fundamentalism. Fundamentalism emerged as the strongest predictor of the acceptance of reactive violence. Both fundamentalism and orthodox religiosity were positive predictors of active violence. However, these latter effects should be interpreted with caution due to the naturally low acceptance of active violence. Finally, the deprivation-radicalization association was stronger for participants scoring higher on fundamentalism, while medium to high orthodox religiosity was the key factor connecting deprivation to radicalization.Implications are delineated regarding practical strategies, specifically formulated for addressing feelings of deprivation within minority contexts.